2021
DOI: 10.1089/mdr.2020.0298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multidrug-Resistant Biofilm-Producing Escherichia coli and Klebsiella pneumoniae in Healthy Cattle and Cattle with Diarrhea

Abstract: This study describes comparative occurrence and characterization of multidrug-resistant (MDR) Escherichia coli and Klebsiella pneumoniae (KP) in healthy cattle (HC) and cattle with diarrhea (DC) in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
0
15
1
Order By: Relevance
“…Eighty-nine isolates from calf diarrhea, including 52 (81.3%) E. coli and 37 (90.2%) S. enterica , showed the MDR phenomenon. However, Bandyopadhyay et al [ 6 ] reported a lower MDR rate (12.3%) of E. coli strains isolated from calves with diarrhea than in the current study. Moreover, in line with the current study, Gebeyehu et al [ 32 ] from Ethiopia reported a 100.0% resistance rate to ampicillin and a 100.0% susceptibility rate to ciprofloxacin among Salmonella strains isolated from raw cow milk samples.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Eighty-nine isolates from calf diarrhea, including 52 (81.3%) E. coli and 37 (90.2%) S. enterica , showed the MDR phenomenon. However, Bandyopadhyay et al [ 6 ] reported a lower MDR rate (12.3%) of E. coli strains isolated from calves with diarrhea than in the current study. Moreover, in line with the current study, Gebeyehu et al [ 32 ] from Ethiopia reported a 100.0% resistance rate to ampicillin and a 100.0% susceptibility rate to ciprofloxacin among Salmonella strains isolated from raw cow milk samples.…”
Section: Discussioncontrasting
confidence: 81%
“…Farm animals such as cattle are known reservoirs for multidrug resistance (MDR) bacteria such as E. coli [ 6 ]. The MDR phenomenon has increased worldwide and is considered a public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extensive resistance in many of the Gramnegative bacteria, these pathogens are considered as a priority for R&D and antimicrobial drug discovery platforms, to facilitate the development of new antibiotics [43]. In addition, continuous monitoring of resistance rates in a given institution or geographical region is another necessity to successfully address AMR globally [44]. Bacteria may present with the MDR/XDR phenotype through the contribution of a variety of mechanisms, including both intrinsic and acquired resistance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Limited epidemiological studies in different parts of the world have revealed that goats, similar to other food animals, can act not only as a mere reservoir but also a potential spreader of the AMR pathogens or antibiotic resistance gene (ARG) through its milk and meat [ 4 , 5 ]. AMR pathogens such as ESBL and carbapenemase producers as well as methicillin-resistant and vancomycin-intermediate Staphylococcus aureus have been reported in different food and companion animals, including goats [ 6 , 7 , 8 ]. Altogether, the recent observations illustrate such a radical shift in perspective that goat farming can no longer be considered a farming system in isolation that presents no or minimum loads of AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, the recent observations illustrate such a radical shift in perspective that goat farming can no longer be considered a farming system in isolation that presents no or minimum loads of AMR. Recently, we reported a higher proportion of resistant pathogens in cattle with diarrhoea than their healthy counterparts [ 8 ]. Diarrhoea, a multifactorial condition, is not uncommon in goats and often requires antimicrobial or antiparasitic intervention.…”
Section: Introductionmentioning
confidence: 99%